Short and simple sequences favored the emergence of N-helix phospho-ligand binding sites in the first enzymes - Longo, Liam M. (Proc Natl Acad Sci U S A, 2020)
The ubiquity of phospho-ligands suggests that phosphate binding emerged at the earliest stage of protein evolution. To evaluate this hypothesis and unravel its details, we identified all phosphate-binding protein lineages in the Evolutionary Classification of Protein Domains database. We found at least 250 independent evolutionary lineages that bind small molecule cofactors and metabolites with phosphate moieties. For many lineages, phosphate binding emerged later as a niche functionality, but for the oldest protein lineages, phosphate binding was the founding function. Across some 4 billion y of protein evolution, side-chain binding, in which the phosphate moiety does not interact with the backbone at all, emerged most frequently. However, in the oldest lineages, and most characteristically in αβα sandwich enzyme domains, N-helix binding sites dominate, where the phosphate moiety sits atop the N terminus of an α-helix. This discrepancy is explained by the observation that N-helix binding is uniquely realized by short, contiguous sequences with reduced amino acid diversity, foremost Gly, Ser, and Thr. The latter two amino acids preferentially interact with both the backbone amide and the side-chain hydroxyl (bidentate interaction) to promote binding by short sequences. We conclude that the first αβα sandwich domains emerged from shorter and simpler polypeptides that bound phospho-ligands via N-helix sites.